The Organizational Peculiarities of Musical Performance of Primary School Pupils in the Carpathian Region - Ivasyshyn, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The Ukrainian Carpathian Mountains are a unique European region. In the Carpathians there are more than half of the species of the flora and fauna of Ukraine. Rapid rivers, shoeless meadows, silvery waterfalls, and the incredible beauty of the landscape – all this creates an extraordinary rise in the human soul who has ever travelled to the Carpathians. Among natural landscapes only mountain ones have an amazing ability to cause human palette of the highest and deepest feelings. The article is devoted to the solution of the problem of relationship of a humanbeing and nature and the aesthetic influence of the landscape of the Carpathian Mountains on musical performance. The article also highlights the role of providing the aesthetic values of the landscape of the Carpathian Mountains in the practice of school work with primary school pupils. The author pays attention to the influence of the landscape on the art of Hutsulschyna. The unique environment and culture of Hutsulschynaare worth of preserving them for the next generations. Therefore the problem of saving and use of the landscape potential of the Carpathians is one of the most important issues for Ukraine in the field of cultural development.